Mullard educational service / [filem jalur] - Carter, Harley (London : Mullard)
Contents : 1. An Introduction to electronics -- 2. Electronic devices : semiconductor devices -- 3. Basic valve circuits, parts 1-4 -- 4. Principles of the cathode ray tube, parts 1-2 -- 5. Themeaning of valve characteristics -- 6. The manufacture of junctiontransistors -- 7. The manufacture of cathode ray tubes -- 8. Oscullators, parts 1-4 -- 9. Modulation and modulators, parts 1-2